Integrative Review of Disparities in Mode of Birth and Related Complications among Mexican American Women. (27th December 2021) - Spurlock, Elizabeth Jones; Kue, Jennifer; Gillespie, Shannon; Ford, Jodi; Ruiz, R. Jeanne; Pickler, Rita H.
Abstract : Introduction: Cesarean rates are particularly high among Hispanic women in some regions of the United States, placing a disproportionate health burden on women and their newborns. This integrative review synthesized the literature on mode of birth (vaginal vs cesarean) and related childbirth complications (hemorrhage, surgical site infection, perineal trauma) among Mexican American women living in the United States. Methods: Four electronic databases, PubMed, Embase, CINAHL, and SCOPUS, were searched to identify studies meeting the inclusion criteria, research studies that included Mexican American women who were pregnant or postpartum. Results were limited to English language and publications that were peer‐reviewed and published before May 2020. Covidence was used in article identification, screening, and assessment. Critical appraisal of the research was performed using the Quality Assessment Tool for Studies with Diverse Designs. Results: Ten articles met inclusion criteria. In some studies, Mexican American women born in the United States were more likely to have cesareans than women born in Mexico; in other studies, these findings were reversed. Mexican American women often had lower unadjusted cesarean rates compared with non‐Hispanic white women, but adjusting for birth facility (some facilities perform more cesareans than others), sociodemographic, and risk factors often revealed Mexican American women have a higher adjusted risk for cesarean birth. Women with higher socioeconomic status had higher cesarean rates compared with women with lower socioeconomic status. In studies of birth outcome by level of acculturation, women who were US‐oriented had higher rates of cesarean and more frequent perinatal complications. By ethnic subgroup, rates of cesarean and complications varied among Hispanic women. Discussion: Birth facility was associated with perinatal outcomes for Mexican American women; those who gave birth at higher‐performing facilities had better outcomes when compared with women who gave birth at lower‐performing facilities. After adjusting for pregnancy complications, Mexican American women had a greater risk for cesarean birth compared with non‐Hispanic white women, a finding that may have clinical practice implications. Level of acculturation affected birth outcomes, but more research using precise instruments is needed.